STUDI PENANGGULANGAN KEMISKINAN KOMUNITAS ADAT TERPENCIL (KAT) DI KECAMATAN RIO PAKAVA KABUPATEN DONGGALA - Rifai, Muhammad (Katalogis, 2016)
This study aims to analyze the characteristics of the Remote Indigenous Communities (KAT), evaluates the condition and handling practices that have been taken by the government as well as the obstacles encountered during the process of empowerment KAT since 2010-2014, formulate a poverty reduction strategy is right for KAT in the district of Rio Pakava. As this study is categorised as survey research, data were obtained by conducted interview with respondents using interview guidelines, and the list of questionnaire.Â This study apply quantitative. Then, Microsoft Excell is used as tool to analyse the data of this study. This study found that the characteristics of existing poverty in the district of Rio Pakava (KAT ) include (1) human resources issues, there are some key issues in this obstacle, namely: Education and Knowledge, Technology, Health, and past orientation of KAT society; (2) KAT programs that had been done since 2010-2014 are: renovating facilities and Infrastructure, improving Education, Health Care, activities in the Remote and Border, Road Infrastructure to remote indigenous community area (KAT), Improving Agricultural Extension Activity and Economic Empowerment; (3) Based on the analysis found that the IFE and EFE matrix IFE's total of strength is higher than weakness by 3.90592, which means that the District of Rio Pakava fully able to overcome the existing weaknesses by using the advantages to reduce poverty in remote indigeneous (KAT) area. Moderate to EFE matrix was found that the factor of chance based on the calculation is equal to 2.78101, with the difference in value between the total score of the opportunities and threats is 0.89481. This shows that the respondents give a high response to the opportunity factor and lower response to threat factor. The total value weighted for external strategic factor by 2.78101, mean that the District of Rio Pakava can take advantage of existing opportunities and avoid the threat of poverty alleviation efforts for KAT; and (4) Based on the matrix of IFE and matrix EFE, suitable formulation strategy to reduce poverty for KAT in the district of Rio Pakava with SWOT analysis, as follows: Building partnerships and cooperation by utilizing local natural resources that exist, Using customs and culture as a bond to strengthening the unity and cohesion, more intensively to disseminate to the public about the creative economy, agriculture and PKAT, Optimizing all the potential that exists to address accessibility issues to remote indigenous area KAT and improving all the existing facilities and infrastructures. The recommendation of this study is to further optimize the system of mentoring as one of the factors supporting the success of this program.